Disrupted and Stretched Linearity in Stephen Sondheim’s Company - Braae, Nick (Schweizer Jahrbuch für Musikwissenschaft, 2026)
This article analyses Stephen Sondheim’s treatment of time in his seminal 1970-musical Company. I argue that his score presents two distinct temporal modes: disrupted linearity, whereby goal-directed motion is interrupted; and stretched linearity, whereby goal-directed motion is extended. These novel temporal categories are illuminated with respect to a range of songs from the show, with explanation as to how different musical parameters contribute to these experiences of time. I conclude by suggesting that this approach to time forms a backdrop to the unconventional narrative structure and thematic material, both of which resist chronological and linear characteristics.